Influence of postoperative radiotherapy target volumes in unilateral head and neck carcinoma of unknown primary: A multicentric study using propensity score. (July 2021) - Brenet, Esteban; Philouze, Pierre; Schiffler, Camille; Pommier, Pascal; Crozes, Carole; Benzerdjeb, Nazim; Monchet, Elodie; Boulagnon-Rombi, Camille; Ton Van, Jean; Podeur, Fabien; Servagi-Vernat, Stéphanie; Liem, Xavier; et al.
Highlights: Management of HNCUP remains controversial due to the lack of randomised trials. Comparing postoperative unilateral nodes vs bilateral nodes + pan mucosal irradiation. A propensity score was built to reduce differences between groups. OS, SS and LRFS did not differ significantly between the groups. Abstract: Objective: To compare the impact of two radiation modalities on loco-regional control, survival and tumour emergence, after node dissection for an unilateral head and neck carcinoma of unknown primary (HNCUP). Materials and methods: This is a multicentric retrospective study of 138 patients with unilateral HNCUP treated between 2002 and 2017. The absence of primary tumour was assessed by a systematic panendoscopy and positron emission tomography. Neck dissection was initially performed for all patients. Radiation Therapy was delivered on ipsilateral lymph node areas in 62 cases (44%: UL-RT group) and on bilateral lymph node areas and the entire pharyngeal mucosa in 77 cases (56%: COMP-RT group). Impact of radiation modalities on locoregional control and overall survival was assessed using propensity score matching method in order to balance baseline characteristics between the two groups. Results: The population included 80.4% men, 80.4% smokers, 32.6% P16 positive tumours and 71.0% extracapsular extension. After a median follow-up of 5 years, the locoregional control rate was 80.3% in the UL-RT group and 75.3% in the COMP-RT group ( p = 0.688). The corresponding rate of contralateral lymph node recurrence was 0% versus 2.6% ( p = 0.503) and the rate of tumour emergence was 11.5% versus 9.1% ( p = 0.778). No significant difference was observed between the UL-RT and the COMP-RT groups for overall survival ( p = 0.9516), specific survival ( p = 0.4837) or tumour emergence ( p = 0.9034). Conclusion: UL-RT seems to provide similar outcomes as COMP-RT in unilateral HNCUP post-operative management.